Investigation on temperature uniformity control of titanium extrusion in hot stretch bending process. Issue 1 (1st December 2022) - Cao, F C; Liu, B S; Zeng, Y S; Wu, W; Wang, Y J
Abstract : Regarding to the impact of temperature on springback in hot stretch bending (HSB) process, this work proposed an investigation on temperature uniformity control of titanium extrusion in HSB process based on the mould which can be elevated by resistance heating. Prior to the HSB test, mould structure was designed to fit for resistance heating. Coupled thermal electrical structural finite element model of HSB process was created in ABAQUS. Resistance heating and HSB tests were performed using displacement control electrically assisted stretch bending machine. The results of simulation indicate that the temperature uniformity of titanium extrusion and the forming accuracy of curved part can be effectively improved by increasing the initial temperature of mould. At last, the curved part of titanium extrusion with L-section was achieved, and the forming accuracy of which was measured and evaluated.